The Italian Constitutional Court’s case law concerning the legitimate expectation of individuals for a monetary compensation for injuries and disabilities brought on by freely assumed vaccinations (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The purpose of the study is to examine the Italian Constitutional Court’s case law concerning a person’s right to monetary compensation for injuries and disabilities brought on by freely assumed vaccinations.
Keywords: Monetary compensation; recommended vaccinations; legitimate expectation; solidarity; Italian Constitutional Court’s case law